THE DEVELOPMENT OF SMALL-SCALE BUSINESS IN RUSSIA, TYPES OF FUNDING - Kirill O. Voronin (Статистика и экономика)
In Russia small-scale business originated in the end of 1980s duringRestructuring. It has been developing as fast as Russian economics.Unlike large industrial companies, which just continued to run businessas they used to, small-scale businessmen had to start from scratch ordisafﬁliate with large organizations. Basically, in 1990-s small-scale business as a ﬁnancial institute was self-regulated due to its highcriminalization and nonpayment of tax.For a period of only 25 years small-scale business has improved muchand now provides well-being to the country. The improvement happeneddue to the following factors:- propitious economic and political climate of the country against thebackground of global economy and the years of restricting- important and useful measures for economic development were taken - important and useful measures for development of small-scale enterprises were takenThe development of this new ﬁnancial institute is quite fast, but historyhas other examples of such phenomenon. In the 21st century RussianFederation adopted experience of advanced countries and imposed it onits historic experience. However, we can’t say that small-scale business is on its top of development in our country. Nowadays development of small-scale business is one of the priorities of the Russian government.